Effects of a new fermented soya bean meal on growth performance, serum biochemistry profile, intestinal immune status and digestive enzyme activities in piglets. Issue 5 (10th October 2021) - Liu, Xuzhou; Ju, Ying; Huang, Liling; Liu, Mingzhi; Bo, Jianing; Zhou, Tongyu; Zhang, Yufeng; Liu, Chuang; Feng, Mingming; Zhang, Shuai; Yan, Yong
Abstract: Background: Fermented soya bean meal (FSBM) is believed to have improved nutritional qualities compared with soya bean meal (SBM) and is also cheaper than soya protein concentration (SPC) and fish meal (FM). Therefore, the present study was conducted to compare the effects of FSBM replacing SBM, SPC and FM in diets on growth performance, serum biochemistry profile, short‐chain fatty acid concentrations in digesta, intestinal mucosal enzyme activities, intestinal proinflammatory cytokine concentrations and morphology in weaned piglets. One hundred and twenty 28‐day‐old piglets (Duroc × Landrace × Yorkshire, body weight: 6.73 ± 1.14 kg) were randomly allocated to four treatment diets (six replicate pens with five piglets per pen) containing SBM, SPC, FM or FSBM as the protein source, respectively. Results: Dietary FSBM supplementation improved average daily gain ( p  < 0.05), gain to feed ratio ( p  < 0.05), and digestibility of dry matter, gross energy, crude protein and organic matter ( p  < 0.05) in pigs compared with those fed SBM during 0–14 days and reduced diarrhoea rate ( p  < 0.05) compared with those fed SBM and FM during 0–14 days. Moreover, pigs fed FBSM had greater IgA and IgM contents and antioxidase activities than those provided SBM and SPC on day 14. In addition, the butyrate concentration in the cecum of pigs fed FSBM was greater than those fed the other diets ( p  < 0.05), and the trypsin activity in duodenum and jejunum of pigs provided FSBM was greater than those fed SBM ( p  < 0.05). Moreover, higher villus height ( p  < 0.05) and villus height to crypt depth ratio ( p  < 0.05) and lower crypt depth ( p  < 0.05) in the duodenum of pigs fed FSBM were observed, and pigs fed FSBM had a lower ( p  < 0.05) TNF‐α concentration in jejunum compared with those fed SBM. Conclusions: In conclusion, dietary FSBM supplementation to replace SBM, SPC and FM could improve piglets' growth performance, intestinal health and immune function.